Real-time polarization-sensitive optical coherence tomography data processing with parallel computing - Liu, Gangjun; Zhang, Jun; Yu, Lingfeng; Xie, Tuqiang; Chen, Zhongping (Applied optics. Optical technology and biomedical optics, 2009)
With the increase of the A-line speed of optical coherence tomography (OCT) systems, real-time processing of acquired data has become a bottleneck. The shared-memory parallel computing technique is used to process OCT data in real time. The real-time processing power of a quad-core personal computer (PC) is analyzed. It is shown that the quad-core PC could provide real-time OCT data processing ability of more than 80 K A-lines per second. A real-time, fiber-based, swept source polarization-sensitive OCT system with 20 K A-line speed is demonstrated with this technique. The real-time 2D and 3D polarization-sensitive imaging of chicken muscle and pig tendon is also demonstrated.